Comparative and evolutionary analysis of RIP kinases in immune responses - Lv, Shangge; Jiang, Yu; Li, Yuzheng; Huang, Ruilin; Peng, Lingyu; Ma, Zhaoyin; Lu, Nan; Lin, Xiaoying; Yan, Jie (Frontiers in Genetics, 2022)
The group of receptor-interacting protein (RIP) kinases has seven members (RIPK1–7), with one homologous kinase domain but distinct non-kinase regions. Although RIPK1–3 have emerged as key modulators of inflammation and cell death, few studies have connected RIPK4–7 to immune responses. The divergence in domain structures and paralogue information in the Ensembl database have raised question about the phylogeny of RIPK1–7. In this study, phylogenetic trees of RIPK1–7 and paralogues constructed using full-length amino acid sequences or Kinase domain demonstrate that RIPK6 and RIPK7 are distinct from RIPK1–5 and paralogues shown in the Ensembl database are inaccurate. Comparative and evolutionary analyses were subsequently performed to gain new clues about the potential functions of RIPK3–7. RIPK3 gene loss in birds and animals that undergo torpor, a common physiological phenomenon in cold environments, implies that RIPK3 may be involved in ischemia-reperfusion injury and/or high metabolic rate. The negligible expression of RIPK4 and RIPK5 in immune cells is likely responsible for the lack of studies on the direct role of these members in immunity; RIPK6 and RIPK7 are conserved among plants, invertebrates and vertebrates, and dominantly expressed in innate immune cells, indicating their roles in innate immunity. Overall, our results provide insights into the multifaceted and conserved biochemical functions of RIP kinases.